Liposomal enhancement of the immunogenicity of adenovirus type 5 hexon and fiber vaccines. - Kramp, W J (1979)
Immunogenicity of adenovirus capsid proteins carried in liposomes was comparable to that with equivalent doses administered in Freund adjuvant, and both forms were more potent than aqueous vaccines.